Corporate tax avoidance : determinants of effective tax rate (ETR) of multinational corporations in Malaysia - Fazliza, Mohd Kasim (2016)
Corporate tax collection is the highest contributor to the revenue for the Malaysian Government as compared to other direct taxes. Likewise, multinational corporations' (MNCs') contribution in terms of corporate taxes in generating the government's tax revenues is also significant particularly for the developing countries including Malaysia. Although there is an increase in the totals collection of direct taxes over the years, the Inland Revenue of Malaysia (IRBM) is concerned with the issue of the tax avoidance as the number of the tax defaulters is on an increasing trend. Thus, this study attempts to examine the determinants of MNCs tax avoidance by looking at their effective tax rates (ETRs). This study utilized the tax return form data from the IRBM to model the effective tax rates (ETRs) of the MNCs in Malaysia, as a proxy of the tax avoidance. The findings suggest that MNCs in Malaysia can be associated with the tax avoidance since their ETRs are below the statutory tax rates (STRs) as stipulated under the Income Tax Act 1967. The results also suggest firm's size, profitability, extensiveness of foreign operation, capital intensity and leverage are the determinants of the tax avoidance of MN Cs in Malaysia. However, this study does not provide evidence on the significant influence of sector effect and location of the holding company on MNCs' tax avoidance in Malaysia.